BIOREMEDIATION OF SALINIZED SOILS BY THE LICHEN CLADONIA SUBSTELLATA FOMENTED BY A NITROGEN SOURCE AND GAMMA RADIATION - Lima, Deyvson Natanael dos Santos; Silva, Andrezza Karla de Oliveira; Silva, Nicácio Henrique da; Pereira, Eugênia C (Ra’e Ga: o Espaço Geográfico em Análise, 2020)
Inadequate management of irrigation techniques has caused salinization of soils in the semiarid region of Pernambuco. With this in mind, the main objective of this study was to evaluate the capacity of the lichen Cladonia substellata, associated with a nitrogen source or gamma radiation, as a possible bioremediator of Fluvic Neosols, salinized by unsupervised irrigation on Assunção Island, Cabrobó County, Pernambuco. Collections of the lichen and soil were carried out to elaborate the experiments, under laboratory conditions. A laboratory control was designed and five treatments, submitted to gamma radiation, or a nitrogen source (urea) at different concentrations, in three sampling groups, in triplicate. Fifteen, transparent glass domes were used, where soil samples (500 g) were placed and lichen thalli (8 g) superimposed. Sample collections were performed every 60 days, for 11 months. Chemical analyses for the quantification of phenolics produced by the lichen and percolated into the soil were developed through spectrophotometry and reaction with FeCl3. At the beginning and end of experiments, the chemical fertility of soils from different treatments was evaluated. It was evidenced that gamma radiation causes more effects on the lichen, singly, than in association with urea. Hyperproduction of lichen phenolics, with percolation to the substrate was achieved, which caused chemical modification of the soil, such as an increase of Ca, Mg, P and Na content, as well as pH. It is possible to affirm that C. substellata,in association or not with an exogenous nitrogen source, is capable of, in the short term, chemically altering soils degraded by salinization, increasing the bioavailability of elements essential to plants and soil organisms.